Force Dynamics and Causation in Akan - Duah, R.A. (University of Ghana, 2013)
This study investigates the expression of force-dynamics in Akan (Talmy 2000). Two main types of causatives can be found in the language, namely non- periphrastic causatives (lexical causatives and cause-effect SVCs) and periphrastic causatives (analytic causatives). The study examines the syntactic properties of causatives and shows that while lexical causatives and cause-effect SVCs involve a monoclausal structure, the analytic causative displays a complex (bi-clausal) structure. In Akan, the difference in the coding of the causee argument in analytic causatives is neither coincidental nor superficial but points to a difference in syntactic properties and structure. It is argued that the different syntactic marking of the causee argument in Akan causatives is not predicted by a syntactic case hierarchy as claimed by Comrie 1976 neither is it motivated by the degree of agentivity of the causee in the causative interaction as Cole 1983 proposed. Rather, the alternative marking of the causee is as a result of restructuring of a complement causative sentence into a partial lexicalised serial verb construction in the language. Five event types of causation are identified namely, MANIPULATION, CREATE, TRIGGER, PROMPT and ALLOW and their properties analysed through Talmy’s (2000) force-dynamics framework. The notion of direct and indirect causation is also examined in Akan. It is emphasized that, at least in Akan, it is better to map event type of causation with the notion of (in)directness of causation because a single causative expression may involve more than one event type of causation.
Thesis (PhD) - University of Ghana, 2013
Keywords: Akan; Syntactic; Lexical Causatives; Analytic Causatives